Emergency Laparoscopic Repair of Giant Left Diaphragmatic Hernia following Minimally Invasive Esophagectomy: Description of a Case and Review of the Literature - Enrico Erdas; Gian Luigi Canu; Luca Gordini; Paolo Mura; Giulia Laconi; Giuseppe Pisano; Fabio Medas; Pietro Giorgio Calò (Case Reports in Surgery)
Postoperative diaphragmatic hernia (PDH) is an increasingly reported complication of esophageal cancer surgery. PDH occurs more frequently when minimally invasive techniques are employed, but very little is known about its pathogenesis. Currently, no consensus exists concerning preventive measures and its management. A 71-year-old man underwent minimally invasive esophagectomy for esophageal cancer. Three months later, he developed a giant PDH, which was repaired by direct suture via laparoscopic approach. A hypertensive pneumothorax occurred during surgery. This complication was managed by the anaesthesiologist through a high fraction of inspired O2 and several recruitment manoeuvres. The patient remained free of hernia recurrence until he died of neoplastic cachexia 5 months later. Laparoscopic repair of PDH may be safe and effective even in the acute setting and in the case of massive herniation. However, surgeons and anaesthesiologists should be aware of the risk of intraoperative pneumothorax and be prepared to treat it promptly.